Skupno etično odločanje zdravstvenih delavcev: pregled literature - Lasič, Darja; Kalender Smajlović, Sedina (Obzornik zdravstvene nege, 2023)
Introduction: Making shared ethical decisions about patients’ further healthcare involves coordinating the opinions of healthcare professionals, and patients and their relatives. The purpose of the research was to examine the joint ethical decision-making of healthcare professionals. Methods: A review of the scientific literature performed in the COBISS, Springer Link and PubMed databases was used. To search for literature in the Slovenian language, the following words were used: "etika", "zdravstveni delavci", "skupne odločitve" and in the English language: "ethics", "health professionals", "shared decision making". The literature review was carried out using the PRISMA diagram. Results were synthesized using thematic analysis. Results: 19 articles were included in the final analysis. We created three thematic categories: (1) ethical competence of healthcare workers, (2) problems in the area of joint ethical decision-making and (3) new approaches to joint ethical decision-making to improve outcomes in clinical practice. In the field of joint ethical decision-making of healthcare professionals, the importance of ethical competence, issues in the field of joint ethical decision-making and new approaches to joint ethical decision-making for improving results in clinical practice is demonstrated. Discussion and conclusion: The findings of the research contribute to illuminating the importance of joint ethical decision-making and giving an insight into the factors of joint ethical decision-making. The end result of certain ethical decisions that affect the interaction of healthcare professionals and all levels in healthcare are important.